Nonnegative trigonometric polynomials - Dimitrov, Dimitar K. [UNESP]; Merlo, Clinton A. [UNESP] (Springer Nature, 2002)
An extremal problem for the coefficients of sine polynomials, which are nonnegative in [0,π] , posed and discussed by Rogosinski and Szego is under consideration. An analog of the Fejér-Riesz representation of nonnegative general trigonometric and cosine polynomials is proved for nonnegative sine polynomials. Various extremal sine polynomials for the problem of Rogosinski and Szego are obtained explicitly. Associated cosine polynomials k n (θ) are constructed in such a way that { k n (θ) } are summability kernels. Thus, the L p , pointwise and almost everywhere convergence of the corresponding convolutions, is established. © 2002 Springer-Verlag New York Inc.
Keywords: Nonnegative trigonometric polynomials, Extremal polynomials, Summability kernel, Fejér-Riesz-type theorem, Lp Convergence, Pointwise and almost everywhere convergence